Characterization of oil palm decanter cake (OPDC) and comparison of residual crude palm oil recovery from OPDC using d-limonene and n-hexane / Naimah Sahad - Sahad, Naimah (2015)
Oil palm decanter cake (OPDC) is one of the abundance biomass wastes generated from oil palm industry. This research investigated the physicochemical properties of OPDC that contribute to the oil loss and the use of d-limonene as green solvent to recover the oil loss in the OPDC using conventional Soxhlet extraction and ultrasonic assisted extraction (UAE). In this study, the OPDC was characterized by having several key properties i.e. high moisture content, high biodegradability and rich in nutrient contents‘ The results also demonstrate that the OPDC exhibits amphiphilic properties, as it is both oleophilic and hydrophilic in nature i.e. low contact angle and has high affinity t0 oil and water. The contact angles were influenced by the surface area and porosity of OPDC. This characterization study has revealed the key factors that contribute to the high oil loss in the OPDC. From the microscopic observation, the majority of residual crude palm oil (RCPO) droplets were less than 50µm. During typical palm oil mill processing, these small oil droplets are difficult to remove via mechanical extraction Using solvent extraction, the residual oil content (IO-16%, dry basis) in OPDC was fully recovered (100% recovery). This study also revealed the use of d-limonene for the RCPO recovery was comparable with n-hexane; in terms of solvent recovery (more than 90%), fatty acids composition, and quality of oils. Besides, the use of UAE was able to overcome the drawbacks of conventional Soxhlet extraction i.e. reduced the solvent consumption from 300 mL to 100 mL; gave shorter extraction time, from 8 hours to 44 minutes; and operated at lower temperature 49°C.